Characterization of hairs and pappi from Cynara cardunculus capitula and their suitability for paper production - Gominho, Jorge (2015)
The capitula of Cynara cardunculus contain hairs and pappi representing 7% of the total plant biomass. These low density biomass components could be mechanically separated without apparent losses using a whole-plant processing prototype. Hairs and pappi are filamentous structures made up of longitudinally aligned fibre cells, without intercellular voids or pitting, with the following dimensions regarding length, width and wall thickness: 1.35mm, 19.8, and 4.8 m for hairs and 1.78mm, 10.4, and 2.9 m for pappi. Chemically hairs and pappi have low content of ash (1.9% and 1.1%, respectively), extractives (5.4% and 6.0%) and lignin (10.6% and 17.8%), and high content of holocellulose (77.5% and 72.8%) and -cellulose (55.2% and 46.8%). Pulps could be produced using a conventional kraft process with high yields and low residual lignin, e.g. 63% at Kappa 7 for hairs and 48% at Kappa 11 for pappi, low coarseness values (0.04 and 0.03mgm−1) and adequate pulp properties for paper (40 and 42Nmg−1 tensile index; 3.6 and 3.4 kPam2 g−1 burst index in unrefined pulps of hairs and pappi, respectively). The results also indicated that there is scope for improving pulp quality by optimising pulping conditions to this type of new raw materials. The differences between hairs and pappi may also be further exploited namely the lower lignin content of hairs and the higher slenderness and wall thickness of pappi fibres. The utilization of hairs and pappi may strengthen the differentiated use of biomass fractions of the Cynara plant and its potential as a bioenergy crop.